Humidified High-Flow Nasal Cannula Oxygen Th erapy in Children- A narrative review - Sajith Kesavan; Bala Ramachandran (Wolters Kluwer Medknow Publications, 2016)
Introduction: Heated Humidified High flow nasal cannula (HFNC) is a promising noninvasive respiratory support that is gaining popularity in both adults and children because of excellent patient tolerance and ease of administration in varying etiologies of respiratory distress. Objectives: of the current article are to review the physiology and practical aspects of HFNC and appraise available evidence with regard to the utility of HFNC in Pediatrics. Results: Prospective studies have established safety and feasibility of HFNC in preterm neonates with respiratory distress and infants with bronchiolitis. Studies suggest that it is equivalent to noninvasive CPAP in these conditions and may have some advantages. Recently a randomized control study in adults with acute hypoxemic respiratory failure have shown a mortality benefit, in addition to decreased intubation rates in the severely hypoxemic subgroup. Conclusions: Current evidence suggests that HFNC is a well tolerated and feasible respiratory support across different age groups and indications in the Pediatric ICU and Emergency Room. It is not inferior to the alternate modes of noninvasive positive pressure ventilation and may have some advantages over conventional forms of non-invasive respiratory support.